Crystallization of pineapple skin juice extraction by using spray drying technique: article - Zaimuri, Madihah; Zainal Abidin, Hanafiah (2019)
Pineapple contains bromelain which known to be natural source of bioactive compound that gives benefits to health purposes. However, high moisture content of the fruit makes it easily perishable and difficult to store and handle. In order to overcome this issue, spray drying technique is implement to convert liquid food products into powder form because the dried powder products will have a longer shelf life at ambient temperature, easy to handle and low cost of transportation. In this research, the juice extracted from the skin of pineapple was spraydried and the characterization of the resulting powder was determined. The combined crystallization and drying of pineapple skin juice extraction was performed in a pilot-scale spray dryer with a varying parameters of operating conditions. The spray drying process is unique because it includes both particle formation and drying. Optimization of spray drying process was carried out using different inlet temperatures of 130°C, 140°C and 150°C and maltodextrin concentrations of 15%, 20% and 25 % w/w. The effect of different parameters on physicochemical properties such as powder yield, pH, moisture content, bulk density and soluble solid content was analyzed. This research demonstrates that the effect of inlet temperature and carrier agent concentration play a vital role in determining the physicochemical properties of fruit extract powder.